Water parameters correlated with the zootechnical performance of shrimp Litopenaeus vannamei grown in oligohaline waters - Thiago Brandão Cavalheiro; Juan Carlos Letelier Carvajal; Reinaldo Farias Paiva de Lucena; Carlos Vinícius Carvalho do Nascimento; Thais Teresa Brandão Cavalheiro Ribeiro (Acta Scientiarum. Animal Sciences, 2022)
The present study aimed to correlate the influence of water quality, cultivation time, area, and density of ponds on the zootechnical performance of shrimp Litopenaeus vannamei in oligohaline waters. It was demonstrated that, under the conditions of this research, better control of temperature, pH and water alkalinity can be employed. Ammonia levels were within the normal range and correlated positively with the growth rate (ρ = 0.69859) and production (ρ = 0.66362) of the ponds. There was also a positive correlation between cultivation time and pond density with shrimp weight (ρ = 0.75305 and 0.68933) and pond productivity (ρ = 0.74763 and 0.79367, respectively). Negative correlations were observed between: I) pH with shrimp survival (ρ = -0.73238) and pond production (ρ = -0.68696); II) alkalinity and pond production (ρ = -0.66162). The results show that the cultivation of shrimp L. vannamei in oligohaline waters is viable and there is potential for increased productivity associated with better hydrological monitoring and use of higher density and cultivation time by some producers.